Warning people that they are being microtargeted fails to eliminate persuasive advantage - Fabio Carrella; Almog Simchon; Matthew Edwards; Stephan Lewandowsky (Communications Psychology)
Abstract The practice of microtargeting in politics, involving tailoring persuasive messages to individuals based on personal vulnerabilities, has raised manipulation concerns. As microtargeting’s persuasive benefits are well-established and its use facilitated by AI tools and personality-inference models, ethical and regulatory concerns are magnified. Here, we explore countering microtargeting effects by creating a warning signal deployed when users encounter personality-tailored political ads. Three studies evaluated the effectiveness of warning “popups” against potential microtargeting by comparing persuasiveness of targeted vs. non-targeted messages with and without popups. Using within subject-designs, Studies 1 (N = 666), 2a (N = 432), and 2b (N = 669) reveal a targeting effect, with targeted ads deemed more persuasive than non-targeted ones. More important, the presence of a warning popup had no meaningful impact on persuasiveness. Overall, across the three studies, personality-targeted ads were significantly more persuasive than non-targeted ones, and this advantage persisted despite warnings. Given the focus on transparency in initiatives like the EU’s AI Act, our finding that warnings have little effect has potential policy implications.